Transformações de substratos terpênicos catalisadas por rutênio e heteropoliácidos: síntese de produtos de química fina - Vinicius Vieira Costa (2011)
In the present work, it has been studied the application of silica-supported H3PW12O40 (PW), the strongest heteropoly acid in the Keggin series, for the liquidphase rearrangement of styrene oxide into phenylacetaldehyde. To our knowledge, no attempt to use heteropoly asids as catalysts for this reaction has been made so far. It has been shown that PW/SiO2 is an efficient, environmentally friendly eterogeneouscatalyst for this reaction. Phenylacetaldehyde is an industrially important intermediate for fine chemical synthesis. The reaction occurs in cyclohexane as a solvent under mild conditions with low catalyst loadings and without PW leaching in solution. At 60oC, the yield of phenylacetaldehyde reaches 92 %, with a high catalyst turnover number of up to 20 000. The catalyst is easy to prepare, stable to leaching under reaction conditions, and can be recovered and reused. A simple and efficient synthesis of several highly valuable fragrance and/orpharmaceutical compounds through the liquid-phase isomerization of -pinene oxide in the presence of cerium and tin catalysts has been developed. A remarkable effect of solvent basicity on chemoselectivity allowed direction of the reaction to either transcarveol or trans-sobrerol. Each of these compounds was obtained in nearly 70 % yieldusing an appropriate polar solvent. Solvent basicity affected strongly the product distribution. In acetone, a weakly basic solvent, the reaction over heterogeneous solgel Sn/SiO2 or Ce/SiO2 catalysts gave mainly trans-sobrerol. No leaching of active components occurs under the reaction conditions and the catalysts can be recovered and reused. On the other hand, in dimethylacetamide, which is a basic solvent, thereaction was essentially directed to trans-carveol. Due to leaching problems, the synthesis of trans-carveol was performed under homogeneous conditions using CeCl3 or SnCl2 as catalysts with a catalyst turnover number up to ca. 1100. The method represents one of the few examples of the synthesis of isomers from -pinene oxide,other than campholenic aldehyde, with a sufficient for practical usage selectivity. Finally, the application of functionalized silica-coated magnetic nanoparticles as a support for the immobilization of ruthenium hydroxide has been studied. The Ru(OH)x/SiO2/Fe3O4 material was used as a catalyst for the oxidation of various alcohols with molecular oxygen. In continuation of our ongoing project aimed at adding value to natural ingredients of essential oils, we have studied the oxidation of variousmonoterpenic alcohols (nerol, perillyl alcohol, isoborneol, carveol, menthol, citronellol and isopulegol) to give valuable fragrance aldehydes and ketones. It has been found that Ru(OH)x/SiO2/Fe3O4 is an efficient heterogeneous catalyst for these reactions which is active in the absence of any co-catalysts or additives. Magnetic properties of the material allow for its facile separation from the reaction medium by means of anexternal magnetic field. No leaching of active components to the reaction medium was observed showing that the process is truly heterogeneous.